2002
DOI: 10.1111/j.1939-1676.2002.tb02378.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Mortality and Thromboembolism in Canine Immune‐Mediated Hemolytic Anemia: A Retrospective Study of 72 Dogs

Abstract: Medical records of 72 dogs diagnosed with immune-mediated hemolytic anemia (IMHA) were reviewed to find risk factors for the disease, for mortality, and for thromboembolism. Coagulation data of 32 patients were evaluated for mortality or thromboembolism risk factors. Cocker Spaniels were at increased risk for IMHA (P ϭ .012). Timing of vaccination was not associated with development of IMHA. PCV ranged from 5 to 33%, with a mean of 16 Ϯ 5%. Autoagglutination was present in 42% of the dogs. Platelet counts (n ϭ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
249
5
17

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(286 citation statements)
references
References 22 publications
15
249
5
17
Order By: Relevance
“…VTE is also recognized as a major cause of death in dogs with AIHA[12,33].Post-mortem examinations in 25 dogs with AIHA showed thromboembolism in 80% of cases[33]. In this study on 72 dogs with AIHA, severe thrombocytopenia, serum bilirubin concentration of N 5 mg/dL and hypoalbuminemia were risk factors for thromboembolism.…”
mentioning
confidence: 60%
“…VTE is also recognized as a major cause of death in dogs with AIHA[12,33].Post-mortem examinations in 25 dogs with AIHA showed thromboembolism in 80% of cases[33]. In this study on 72 dogs with AIHA, severe thrombocytopenia, serum bilirubin concentration of N 5 mg/dL and hypoalbuminemia were risk factors for thromboembolism.…”
mentioning
confidence: 60%
“…In people, vaccination has been suggested as a trigger for the development of immune-mediated cytopenias (Chen and others 2001) and a study of dogs with imha suggested a similar relationship (Duval and Giger 1996). However, in another retrospective study of dogs with imha , vaccination was not associated with the development of the disease (Carr and others 2002). …”
Section: Discussionmentioning
confidence: 99%
“…The variables were chosen either on the basis of their significance in previous studies or on a biological basis (Klag and others 1993, McManus and others 2001, Carr and others 2002). Correlations between the dogs' treatment and period of hospitalisation and outcome were evaluated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent vaccination may also have played a role in triggering the IMHA. The relationship between vaccination and IMHA remains unproven, with one study suggesting a temporal association between vaccination and the onset of IMHA (Duval and Giger 1996) and other studies where such an association was not found (Carr and others 2002, Weinkle and others 2005). There are few reports of IMHA developing within days of vaccination in dogs (Duval and Giger 1996) and most of the studies evaluating a possible temporal association between the two assess the four-week period following vaccination.…”
Section: Discussionmentioning
confidence: 99%